The impact of the urbanized environment on the example on some physiological indicators (Thuja occidentalis) of the city of Minsk - Bondaruk, Roman S. (Journal of the Belarusian State University. Ecology, 2021)
In large cities a special temperature condition is formed, which is characterized by the increased temperatures that affects the duration of the growing season of plants. A decrease in the relative humidity of the air in the city is of great ecological importance for plants; this is especially noticeable in the summer. In urban conditions, a leveling of winds and the increased turbulence of air flows, which is associated with the planning features of urban development, lead to the accumulation of harmful atmospheric impurities. Smoke and dust content of the air in urban conditions retain up to 20 % of solar radiation, which has an adverse effect on the vital activity of plants. The urban environment is characterized by the features of the light regime, which disrupts the natural biological rhythms. In cities, the soils are exposed by a strong transformation and go through a complex anthropogenic impact. Compaction and contamination of the soil as well as asphalt coating negatively affect the temperature conditions, air and water exchange of the soils, and, as a result, the state of vegetation. The urban environment is distinguished by the originality of environmental factors, the specificity of technogenic impacts, leading to a significant transformation of the environment. Plants are the main factor in the ecological stabilization of the urban environment due to their vital activity, photosynthesis and the ability to accumulate pollutants. In this regard, it seems relevant to study the resistance of various plant species to urban conditions. Assessment of the ecological plasticity of plants and determination of their adaptive potential allows solving various ecological and practical problems. In the process of studying the influence of the urbanized environment on the example of the city of Minsk on some physiological indicators of thuja occidentalis plants, it was found that a change in cellular metabolism manifests itself in an increase in the permeability of cell membranes, a change in water metabolism of plants, an increase in peroxidase activity by 35% and a decrease in catalase activity by more than 1,6 times.
Keywords: urban environment; catalase; peroxidase; permeability of cell membranes; water exchange